2006
DOI: 10.1158/1078-0432.ccr-06-0176
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog: an Attribute to Tumor Regrowth after Chemoradiotherapy and a Target to Improve Radiation Response

Abstract: Purpose: Despite aggressive chemotherapy, radiotherapy, surgery, or combination approaches, the survival rate of patients with esophageal cancer remains poor. Recent studies have suggested that constitutive activation of the Hedgehog (Hh) pathway in cancers of the digestive tract may contribute to the growth and maintenance of cancer. However, the relationship between Hh signaling and therapeutic response is unknown. Experimental Design: The expression and temporal kinetics of Hh signaling and proliferation bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
115
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(131 citation statements)
references
References 37 publications
(24 reference statements)
10
115
2
Order By: Relevance
“…Based on cancer stem cell theory, one would anticipate that Hh-signaling activation may exert chemotherapy or radiotherapy resistance in cancer if this pathway has a major role in cancer stem cell functions (Reya et al, 2001). Several studies have shown that Hh-signaling activation is associated with chemotherapy resistance or radiotherapy resistance (Sims-Mourtada et al, 2006;Yoshikawa et al, 2008;Olive et al, 2009), supporting that hedgehog signaling activation has a role in cancer stem cell functions. It was recently reported that Hh-signaling inhibitor enhances the delivery of chemotherapy in a mouse model of pancreatic cancer (Olive et al, 2009).…”
Section: Activation Of Hh Signaling In Extracutaneous Tumorsmentioning
confidence: 99%
“…Based on cancer stem cell theory, one would anticipate that Hh-signaling activation may exert chemotherapy or radiotherapy resistance in cancer if this pathway has a major role in cancer stem cell functions (Reya et al, 2001). Several studies have shown that Hh-signaling activation is associated with chemotherapy resistance or radiotherapy resistance (Sims-Mourtada et al, 2006;Yoshikawa et al, 2008;Olive et al, 2009), supporting that hedgehog signaling activation has a role in cancer stem cell functions. It was recently reported that Hh-signaling inhibitor enhances the delivery of chemotherapy in a mouse model of pancreatic cancer (Olive et al, 2009).…”
Section: Activation Of Hh Signaling In Extracutaneous Tumorsmentioning
confidence: 99%
“…Recent studies suggest that SHH signaling activation upregulates the expression of ABCG2 in several cancers. 12,13 Although inappropriate activation of the SHH signaling pathway has been shown in many cancers, SHH proteins have not been assessed in diffuse large B-cell lymphoma, nor have ABCG2 protein levels been assessed in these tumors. Here, we investigated expression of SHH signaling proteins and ABCG2 in diffuse large B-cell lymphoma.…”
mentioning
confidence: 99%
“…The Hh pathway is thought to play an important role in regulating CSC proliferation, survival and maintenance [58][59][60][61][62]. Hh was first discovered in Drosophila and it is a highly conserved pathway across multiple organisms.…”
Section: Cd24mentioning
confidence: 99%
“…All of these reveal the essential role of Hh signaling pathway in controlling the behavior of CSCs and offer new therapeutic possibilities. Although the specific role Hh signaling has in radiation resistance remains an area of active investigation, it is reported that activation of Hh signaling pathway may promote the repopulation of CSCs after radiotherapy, thereby, contributing to both radiation resistance and treatment failure [61]. To determine the role of Hh signaling in therapeutic resistance to radiotherapy, Sims-Mourtada et al analyzed esophageal tumor samples from 43 radiotherapy resistant cancer patients and showed that 83.7% had activated Hh signaling defined by Hh expression and nuclear GLI localization [61].…”
Section: Cd24mentioning
confidence: 99%